A neurophysiological approach to the distinction between motor and cognitive skills: a functional magnetic resonance imaging study - Lu, Yunhang; Kim, Jingu; Kim, Teri (Frontiers in Neuroscience, 2023)
This study investigated the neurophysiological differences underpinning motor and cognitive skills by measuring the brain activity via functional magnetic resonance imaging. Twenty-five healthy adults (11 women, 25.8 ± 3.5 years of age) participated in the study. We developed three types of tasks, namely, simple motor task (SMT), complex motor task (CMT), and cognitive task (CT), using two-dimensional images of Gomoku, a traditional game known as five in a row. When shown the stimulus, participants were instructed to identify the best spot to win the game and to perform motor imagery of placing the stone for the SMT and CMT but not for the CT. Accordingly, we found significant activation from the CMT minus SMT contrast in the dorsolateral prefrontal cortex, posterior parietal cortex, precentral gyrus, and superior frontal cortex, which reflected increased visuospatial attention, working memory, and motor planning. From the CT minus SMT contrast, we observed significant activation in the left caudate nucleus, right medial prefrontal cortex, and right primary somatosensory cortex, responsible for visuospatial working memory, error detection, and cognitive imagery, respectively. The present findings indicate that adopting a conventional classification of cognitive and motor tasks focused on the extent of decision making and motor control involved in task performance might not be ideal.